Implementasi Pendidikan Inklusi dalam Pembelajaran Pendidikan Agama Islam - Nurhadisah Nurhadisah (DAYAH: Journal of Islamic Education, 2019)
SD Negeri (public elementary school) 25 Banda Aceh is one of the schools that join together children with special needs with normal children in one class in every school subject including Islamic religious education. This practice may cause teachers to encounter difficulties in teaching children with special needs; moreover, other problems also occur such as the limited number of teachers of Islamic religious education, inadequate facilities, and so forth. The focus of this research was related to the implementation, the role of teachers, as well as the constraints and solutions of the Islamic religious education teachers in performing the teaching and learning process at SD Negeri 25 Banda Aceh. This qualitative research employed a descriptive research approach. The data were collected through observation, interviews, and documentation. The results showed that the implementation of Islamic religious education learning for children with special needs was based on the 2013 curriculum. The modified curriculum was then grouped into the modifications of learning time allocation, learning materials, and the teaching and learning process of the children with special needs. The methods employed by the teachers were relatively similar to regular children such as memorization, lecture, question and answer, group work, demonstration, and practice. However, children with special needs also required further assistance and motivation. These children would also need a special escort teacher during the teaching and learning process. The roles of the teachers in implementing inclusive education included being correctors, inspirators, informers, organizers, motivators, initiators, facilitators, mentors, demonstrators, classroom managers, supervisors, mediators, and evaluators. In addition, teachers used learning tools and media to support students' understanding, especially in Islamic education learning. The obstacles faced by the teachers were due to the different abilities and characters of the students that made the teachers become very difficult in delivering the materials, the limited number of the teachers, the nonoptimal use of media, facilities, and infrastructure, and lack of study hours. The solutions to these issues included teachers being equipped with a guideline for handling children's special needs by making adjustments of time, manner, and material, and building togetherness, equality, and respect among fellow students.